Step-by-step explanation:
Move expression to the left side and change its sign
5
y
−
3
+
10
y
2
−
y
−
6
−
y
y
+
2
=
0
Write
−
y
as a sum or difference
5
y
−
3
+
10
y
2
+
2
y
−
3
y
−
6
−
y
y
+
2
=
0
Factor out
y
and
−
3
from the expression
5
y
−
3
+
10
y
(
y
+
2
)
−
3
(
y
+
2
)
−
y
y
+
2
=
0
Factor out
y
+
2
from the expression
5
y
−
3
+
10
(
y
+
2
)
(
y
−
3
)
−
y
y
+
2
=
0
Write all numerators above the least common denominator
5
(
y
+
2
)
+
10
−
y
(
y
−
3
)
(
y
+
2
)
(
y
−
3
)
=
0
Distribute
5
and
−
y
through the parenthesis
5
y
+
10
+
10
−
y
2
+
3
y
(
y
+
2
)
(
y
−
3
)
=
0
Collect the like terms
8
y
+
20
−
y
2
(
y
+
2
)
(
y
−
3
)
=
0
Use the commutative property to reorder the terms
−
y
2
+
8
y
+
20
(
y
+
2
)
(
y
−
3
)
=
0
Write
8
y
as a sum or difference
−
y
2
+
10
y
−
2
y
+
20
(
y
+
2
)
(
y
−
3
)
=
0
Factor out
−
y
and
−
2
from the expression
−
y
(
y
−
10
)
−
2
(
y
−
10
)
(
y
+
2
)
(
y
−
3
)
=
0
Factor out
−
(
y
−
10
)
from the expression
−
(
y
−
10
)
(
y
+
2
)
(
y
+
2
)
(
y
−
3
)
=
0
Reduce the fraction with
y
+
2
−
y
−
10
y
−
3
=
0
Determine the sign of the fraction
−
y
−
10
y
−
3
=
0
Simplify
10
−
y
y
−
3
=
0
When the quotient of expressions equals
0
, the numerator has to be
0
10
−
y
=
0
Move the constant,
10
, to the right side and change its sign
−
y
=
−
10
Change the signs on both sides of the equation
y
=
10
Check if the solution is in the defined range
y
=
10
,
y
≠
3
,
y
≠
−
2
∴
y
=
10
Answer:
This true because why ?
Step-by-step explanation:
The first cube can land in any one of 6 ways.
The second cube can land in any one of 6 ways.
Total number of ways that 2 dice can land = (6 x 6) = 36 ways.
For any of these ways, the sum of the numbers rolled is 9 :
3, 6
4, 5
5, 4
6, 3
There are 4 ways to roll a 9, out of a total of 36 ways that
the dice can land. So the probability of rolling a 9 is
4 / 36 = 1 / 9 = <em>11-1/9 percent</em>
Answer:
C. -0.7
Explanation:
Given the equation:
![\frac{1}{2}(-1.4m+0.4)=\boxed{\square}_{}m+0.2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28-1.4m%2B0.4%29%3D%5Cboxed%7B%5Csquare%7D_%7B%7Dm%2B0.2%E2%80%8B)
First, distribute the bracket on the left-hand side:
![\begin{gathered} \frac{1}{2}(-1.4m)+\frac{1}{2}(0.4) \\ =-0.7m+0.2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B1%7D%7B2%7D%28-1.4m%29%2B%5Cfrac%7B1%7D%7B2%7D%280.4%29%20%5C%5C%20%3D-0.7m%2B0.2%20%5Cend%7Bgathered%7D)
The number that makes the given expressions equivalent is -0.7.
The correct choice is C.